Accelerate equitable change by centering adult learner needs. Issue 7 (10th March 2021) - Sutton, Halley
Abstract : Even before the COVID‐19 pandemic hit the world, 44 million adults in the United States were at risk of being left behind by the future of work. "Even before the pandemic, a lot of these adults were struggling, and they certainly weren't equipped to ride out this massive disruption — none of us were, " Melissa Leavitt, Director of Research at the Strada Institute of the Future of Work, said.